Пушкин А.С. - Сурат И.З. (Имя Россия. Исторический выбор, 2008)
Экземпляры: Селтинская районная библиотека (к/х) (20091012) / Инвентарный номер: 196364 / Цена: 188.98 / Авт.знак: С 90 / ГРНТИ: 17 / ББК: 83.3